EVALUASI IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS)DI SMK TELEKOMUNIKASI TUNAS HARAPAN KABUPATEN SEMARANG (STUDI TENTANG PEMBELAJARAN PAKEM) - Prima Widyatmoko; Bambang Ismanto (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study aims at evaluating (a) the design of implementation of PAKEM learning in SMK Telekomunikasi Tunas Harapan, (b) the installation of implementation of PAKEM learning in SMK Telekomunikasi Tunas Harapan, (c) the process of implementation of PAKEM learning in SMK Telekomunikasi Tunas Harapan, and (d) the product evaluation of implementation of PAKEM learning in SMK Telekomunikasi Tunas Harapan. This is a evaluative research employing Discrepency Evaluation Model. Techniques of collecting data used are interview, queationaires, documentations study, and observation. Triangulation technique is used to support data validity. The results of this study are (a) the design of implementation of PAKEM learning has been formulated with regard to educators criteria including input, process, and output aspects, (b) there is still 2% discrepency in teachers’ certificates. Qualifications of teachers’ academic and teachers’ competencies in PAKEM learning are in line with the standards determined, (c) criteria of succesful PAKEM learning program have not been fulfiled entirely. Syllabus and lesson plan preparation reach 85%. Active learning process goes to low discrepency (13%). Creative learning process goes to moderate discrepency (31%). Effective learning process goes to low discrepency (18%). Fun learning process goes to low discrepency (15%). In learning achievement assessment, teachers have done their responsibilities well, (d) the products in PAKEM learning include achievement in affective aspect where 90% students gain predicate “good”, cognitive aspect where 80% students gain B-, and psychomotoric aspect where 79% students gain B-.